Piloplex, a new long-acting pilocarpine polymer salt. B: Comparative study of the visual effects of pilocarpine and Piloplex eye drops. Issue 1 (January 1979) - Mazor, Z; Ticho, U; Rehany, U; Rose, L
Abstract : Induced accommodation and changes in vision (distance and near) were measured monocularly and binocularly in 9 young healthy volunteers in a double blind study after administering to them pilocarpine hydrochloride 4%, Piloplex 3.4, and saline eye drop instillations. Piloplex 3.4, a new long-acting pilocarpine polymer salt, and pilocarpine hydrochloride 4% (both contain equal amounts of pilocarpine-3.4%) induced changes in vision and accommodation. These changes were greater with pilocarpine hydrochloride than with Piloplex. The maximum changes occurred half an hour after instillation and the effect vanished after an additional period up to 3 hours. The changes were greater when measured monocularly than binocularly. Piloplex initiates a prolonged hypotensive effect which lasts for 12 hours. Patients with glaucoma are thus able to use Piloplex on a twice-daily schedule. Consequently, visual disturbances occur only once a day in contrast to pilocarpine hydrochloride given 4 times a day, which induces 3 visual disturbances during the day.